The market for complementary services in the Peruvian electricity sector: regulatory evolution and challenges - Calderón Rojas, Ximena (2025)
This article analyzes the regulatory evolution and regulatory challenges associated with the implementation of Complementary Services in the Peruvian electricity sector, in the context of the recent modification of Law 28832 and taking into account the Chilean comparative experience.In such manner, the current conditions of the regulatory framework and the need to introduce incentives that promote the participation of new actors are examined, especially given the increase in the penetration of intermittent renewable energies.